2003
DOI: 10.1111/1467-6494.t01-1-00001
|View full text |Cite
|
Sign up to set email alerts
|

Personality Judgments in Adolescents' Families: The Perceiver, the Target, Their Relationship, and the Family

Abstract: The present study investigated whether personality judgments involve different processes in a family setting than in a nonfamily setting. We used the Social Relations Model to distinguish the effects of perceiver, target, perceiver-target relationship, and family on personality judgments. Family members of families with adolescents judged their own and the other members' Big Five factors. Judgments were found to depend on the relevance of personality factors within the family setting: Agreeableness and Conscie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 63 publications
(88 reference statements)
4
34
1
Order By: Relevance
“…The simple main SRM effects (actor, partner, relationship, and family effects) for perceived support and for Agreeableness separately will not be described in the present study because they have been addressed in earlier studies (Branje et al, 2002(Branje et al, , 2003. We will focus on the relations between different SRM effects of Agreeableness and perceived support, to address our hypotheses regarding the links between perceived support and Agreeableness across and within family relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple main SRM effects (actor, partner, relationship, and family effects) for perceived support and for Agreeableness separately will not be described in the present study because they have been addressed in earlier studies (Branje et al, 2002(Branje et al, , 2003. We will focus on the relations between different SRM effects of Agreeableness and perceived support, to address our hypotheses regarding the links between perceived support and Agreeableness across and within family relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the SRM makes a sharp distinction between the effects of dispositional characteristics of individuals, the dyadic relationships between individuals, and the family to which those individuals belong. SRM analyses have revealed that both perceived support and Agreeableness in family relationships are a function of characteristics of each partner in a relationship as well as the unique relationship between the partners (Branje, Van Aken, & Van Lieshout, 2002;Branje, Van Aken, Van Lieshout, & Mathijssen, 2003). High actor variance showed that differences in perceived support and Agreeableness of individual family members are to a large extent due to actor effects, or individual family members' disposition to generally perceive support and Agreeableness from other family members.…”
Section: The Social Relations Model and Agreeableness And Support In mentioning
confidence: 99%
“…A Dutch adaptation (Branje, van Aken, van Lieshout, & Mathijssen, 2003) of 30 adjective Big Five personality markers selected from Goldberg (1992) was used to assess the following personality dimensions: Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness. Each scale consisted of six items.…”
Section: Methodsmentioning
confidence: 99%
“…Further, children with behavior problems with normative levels of CU traits report being more angry (Sadeh et al 2009) and show more angry reactivity to provocation from others (Muñoz et al 2008a) but, again, it is not clear if they are perceived by their peers as being more angry than other children. Assessing how peers perceive the child's emotional characteristics could be crucial for understanding the peer relationships of children with behavior problems (Branje et al 2003;Muñoz et al 2008b;Perry-Parrish et al 2012).…”
Section: Introductionmentioning
confidence: 99%